Die Pest und medizinische Literatur des späten Mittelalters - Tomíček, David (Theatrum historiae, 2013)
This paper deals with the question of contagiousness an communicability of plague in the treatises of late medieval physicians and leads to conclusions that beside the generally accepted miasmatic theory (i.e. plague si communicated by aer) two other conceptions were important. First, plague acts like contagious diseases, especially those with clearly visible skin symptoms, is communicable from human to human and dangerous is a mere contact with diseased person or with something witch was in contact with the such person. Second, plague is very similar to poison and is able to spread like this matter.